2012
DOI: 10.1002/pmic.201200202
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric silicon biochips for label and label‐free DNA and protein microarrays

Abstract: Protein and DNA microarrays hold the promise to revolutionize the field of molecular diagnostics. Traditional microarray applications employ labeled detection strategies based on the use of fluorescent and chemiluminescent secondary antibodies. However, the development of high throughput, sensitive, label-free detection techniques is attracting attention as they do not require labeled reactants and provide quantitative information on binding kinetics. In this article, we will provide an overview of the recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 102 publications
0
16
0
Order By: Relevance
“…It has been shown that Si chips are compatible with fluorescence assays and they provide considerable advantages by enhancing the fluorescence signal [ 22 ], thus allowing for a pre-calibration and quality control by IRIS. In light of these advantages, the utility of a calibrated fluorescence enhancement (CaFE) method has been demonstrated in [ 14 , 15 , 23 ] on an integrated platform. Significant improvements have been demonstrated for a particular application involving allergen-specific IgE detection with two major allergens, peanut (Ara h1) and timothy grass (Phl p1), whose immobilization can vary significantly making fluorescence signal calibration vital to obtain accurate results [ 17 ].…”
Section: Applications and Resultsmentioning
confidence: 99%
“…It has been shown that Si chips are compatible with fluorescence assays and they provide considerable advantages by enhancing the fluorescence signal [ 22 ], thus allowing for a pre-calibration and quality control by IRIS. In light of these advantages, the utility of a calibrated fluorescence enhancement (CaFE) method has been demonstrated in [ 14 , 15 , 23 ] on an integrated platform. Significant improvements have been demonstrated for a particular application involving allergen-specific IgE detection with two major allergens, peanut (Ara h1) and timothy grass (Phl p1), whose immobilization can vary significantly making fluorescence signal calibration vital to obtain accurate results [ 17 ].…”
Section: Applications and Resultsmentioning
confidence: 99%
“…Probe density for each immobilised peptide on the array was assessed using label-free film thickness measurement using on the Nanoview platform by nanoQC2.3.2-IT software (NanoView Biosciences, Boston, MA) and previously determined calibration factors for IRIS [43,44]. The average amount of each immobilised peptide was 1.5-3.5 ng/mm 2 .…”
Section: Peptide Microarraysmentioning
confidence: 99%
“…With the introduction of a silicon/silicon oxide (Si/SiO 2 ) substrate, coated with the functional polymer copoly(DMA‐NAS‐MAPS), we have provided a highly sensitive microarray platform with better reproducibility compared to glass slides whose performance was demonstrated in the analysis of sera of 30 adults with sensitization to inhalant allergens . The improved performance of Si/SiO 2 slides with a controlled oxide layer of 100 nm is the result of enhanced fluorescence intensity detected on the surface thanks to constructive optical interference …”
Section: Introductionmentioning
confidence: 99%